Making sense of sex : the new facts about sex and love for young people - Kaplan, Helen Singer 1929- (New York : Simon and Schuster, 1979)
Discusses the biology and psychology of the sexual experience, covering the realities and myths of sex; sexual desire, response, and orgasm; sexual problems; reproduction; birth control; and sexually transmitted diseases.
Includes index.
Keywords: Sex instruction for youth; Sex instruction for youth